2003
DOI: 10.1097/00130404-200301000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of Oral CI-994 in Combination with Gemcitabine in Treatment of Patients with Advanced Cancer

Abstract: The 6-mg/m2 dose of CI-994 (p.o. x 21 days) was defined as the maximum tolerated dose that could safely be administered in combination with gemcitabine (1,000 mg/m2 i.v. on days 1, 8, and 15) during a 28-day cycle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…[7][8][9][10][11][12] In the present study, we describe prodrugs of BA that are HDACIs. These prodrugs inhibit proliferation and induce histone acetylation, differentiation and cell death of human prostate carcinoma cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12] In the present study, we describe prodrugs of BA that are HDACIs. These prodrugs inhibit proliferation and induce histone acetylation, differentiation and cell death of human prostate carcinoma cells in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A number of substances that display HDACI properties are in preclinical and clinical development, including AN-9 (a derivative of BA), the hydroxamic acid SAHA, trichostatin A, the benzamides MS-275 and CI-994 and the cyclic peptides trapoxin and depsipeptide. [7][8][9][10][11][12] For over a decade, we have studied prodrugs of low m.w. aliphatic acids, primarily BA, as potential anticancer agents.…”
mentioning
confidence: 99%
“…In this context, forward chemogenomics strategies are used to initially examine the phenotypic effect of a compound or a panel of compounds on a Applications Chemogenomics strategies are increasingly being harnessed by various fields of medical research -for example, those related to cancer or immune, inflammatory and hormone disease -in attempts to develop new targeted therapies as rapidly as possible (BOX 3). Several advances have been made by chemogenomics in understanding the molecular biology of various diseases and in identifying potential pharmacological and MYELODYSPLASTIC SYNDROME [40][41][42][43][44][45][46] . In turn, phenotypic screening of compounds that have been recently discovered by reverse chemogenomics to inhibit a certain biological pathway can be used to identify the immediate target of compound action in this pathway.…”
Section: Ligand and Target Selectionmentioning
confidence: 99%
“…116 A phase I trial of CI-994 in combination with known anti-cancer drugs such as capecitabine, paclitaxel, carboplatin, or gemcitabine demonstrated that CI-994 was well tolerated in combination therapy. 19,117,118 In the case of hydroxamic acids, a phase I trial of oral SAHA has shown that it is well tolerated, induces histone acetylation, and has anti-tumor activity in solid and hematological tumors. Non-specific constitutional symptoms, including fatigue, anorexia, diarrhea, and dehydration were observed, while myelosuppression and thrombocytopenia were common in IV formulation.…”
Section: Hdacis In Clinical Trialsmentioning
confidence: 99%